2005
DOI: 10.3201/eid1112.041293
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV Infection in a Restaurant from Palm Civet

Abstract: Contact with food animals was associated with SARS-CoV infection in the People’s Republic of China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
232
0
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(253 citation statements)
references
References 16 publications
4
232
0
11
Order By: Relevance
“…In addition, SARS-CoV contains eight encoded accessory genes interspersed amongst the viral structural genes [22,25,126], the most of the known CoVs. Interestingly, these accessory genes are present in SARS-CoVs isolated from bats, civet cats, raccoon dogs, and humans, suggesting important accessory functions in a variety of hosts [55,127,128]. Evidence confirms that these accessory proteins are indeed expressed during SARS-CoV infection, but for many, their functions are yet to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, SARS-CoV contains eight encoded accessory genes interspersed amongst the viral structural genes [22,25,126], the most of the known CoVs. Interestingly, these accessory genes are present in SARS-CoVs isolated from bats, civet cats, raccoon dogs, and humans, suggesting important accessory functions in a variety of hosts [55,127,128]. Evidence confirms that these accessory proteins are indeed expressed during SARS-CoV infection, but for many, their functions are yet to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of infected patients developed severe complications, with 20% developing ARDS (42). However, reported SARS cases have ceased since 2004 as the spread of infection has subsided (43). More recently, the second novel coronavirus, MERS-CoV, led to the Middle East respiratory syndrome (44).…”
Section: Other Viruses Leading To Ardsmentioning
confidence: 99%
“…SARS-CoV shares similar characteristics with MERS-CoV, including likely zoonotic origin and transmission (17)(18)(19)(20). Recent research on MERS-CoV has demonstrated plausibility for zoonotic transmission from dromedary camels to humans (21,22 seems less able than SARS-CoV to spread from personto-person (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 97%